Towards a Better Scoring - Tashev, Ivan; Winters, R. Michael; Wang, Yu-Te; Johnston, David; Estepp, Justin; Bridges, Nathaniel (RAPiD, 2023)
In this paper, we propose a novel method to calculate trainee performance scores in a flight simulator environment using flight simulator logs. Our approach improves upon the existing scoring system designed in the AFRL by better fitting scores into the existing model of the training process.